2002
DOI: 10.1002/pola.10331
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the surface content, hydrolysis ratio, and condensation degree of polyalkoxysiloxane segregated to the surface of a polyurethane crosslinked film by X‐ray photoelectron spectroscopy

Abstract: We report, using an electron spectrometer equipped with both monochromatized Al Kα and unmonochromatized Mg Kα sources, the quantitative characterization of the surface content, hydrolysis ratio, and condensation degree of polyalkoxysiloxane segregated to the surface of a polyurethane crosslinked film consisting of acryl polyol, polyisocyanate, and polyalkoxysiloxane. Unmonochromatized Mg Kα X‐ray irradiation extremely accelerated the decomposition of alkoxy groups of polyalkoxysiloxane. The surface content an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The surface migration of the siloxane segment has also been observed in polyurethane films produced in the presence of a polyalkoxysiloxane 27. The hydrolysis of SiOC bond linkages is followed by silanol condensation, and this produces a low‐surface‐energy siloxane 27…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The surface migration of the siloxane segment has also been observed in polyurethane films produced in the presence of a polyalkoxysiloxane 27. The hydrolysis of SiOC bond linkages is followed by silanol condensation, and this produces a low‐surface‐energy siloxane 27…”
Section: Introductionmentioning
confidence: 92%
“…X‐ray photoelectron spectroscopy of materials with long siloxane segments indicates that the lower surface energy siloxane migrates to the surface of the polymer films 26. The surface migration of the siloxane segment has also been observed in polyurethane films produced in the presence of a polyalkoxysiloxane 27. The hydrolysis of SiOC bond linkages is followed by silanol condensation, and this produces a low‐surface‐energy siloxane 27…”
Section: Introductionmentioning
confidence: 98%
“…Changes in the structure with curing, particularly the surface structure, have also been demonstrated in other systems. Tomita et al 11 reported the use of XPS to study the surface segregation of poly(alkoxysiloxane) additives to polyurethanes during curing. Using Al K␣ X-rays, they were able to quantify the amount of poly-(alkoxysiloxane) at the surface, the hydrolysis ratio, and the degree of condensation.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the structure with curing, particularly the surface structure, have also been demonstrated in other systems. Tomita et al11 reported the use of XPS to study the surface segregation of poly(alkoxysiloxane) additives to polyurethanes during curing. Using Al Kα X‐rays, they were able to quantify the amount of poly(alkoxysiloxane) at the surface, the hydrolysis ratio, and the degree of condensation.…”
Section: Introductionmentioning
confidence: 99%